Pengaruh Karakteristik Pekerjaan Terhadap Kinerja Karyawan dan Kepuasan Kerja Dengan Variabel Moderator Budaya Kerja Pada Badan Keswadayaan Masyarakat (BKM) di Kota Probolinggo - Mardi Astutik; Seger Priantono (Jurnal Manajemen, 2020)
In addition to the characteristics of the work, employee satisfaction is also determined the work culture that occurs in the internal BKM. The work culture at BKM is aimed at creating honest values, mutual respect, responsibility, mutual trust, foster innovation and creativity of employees for the comfort of members, loyal friends, discipline and family. The current development of BKM is driven by the culture of work but on its way, the stability of employees has a turning impact on the work culture that can affect the performance of its employees. The purpose of research to test the influence of occupational characteristics on employee performance and employee satisfaction work with a variable of working culture moderator at BKM in Probolinggo. This research is with causal associative approach, the sample used as many as 120 employees from 29 BKM in the city of Probolinggo. Data analysis with moderated regression analysis. The results showed that the characteristics of the work have a significant effect on employee performance and job satisfaction with the moderator variables of working culture at the Badan Keswadayaan Masyarakat (BKM) in the city of Probolinggo.